Plasticity of Amorphous Alloys: 2. Inhomogeneous Deformation - Park, Kyoung-Won; Lee, Chang-Myeon; Lee, Jae-Chul (KOREAN INST METALS MATERIALS, 2009)
Studies of a number of Cu-Zr amorphous alloys have demonstrated that those exhibiting greater plastic strain during homogeneous deformation at room temperature show lower global plasticity associated with inhomogeneous deformation in a typical compression test. Using a combination of experiments and molecular dynamics simulations, we clarify this seeming paradox between the homogeneous and inhomogeneous deformation by exploring the microstructural. aspects in view of the structural disordering, disorder-induced softening, and shear localization and relate these findings to the global plasticity of bulk amorphous alloys. Additional analyses were conducted to derive a simple structural parameter that allows the prediction of the global plasticity of bulk amorphous alloys.
Keywords: BULK METALLIC-GLASS; CU-ZR SYSTEM; MECHANICAL-PROPERTIES; ATOMIC GLASS; FLOW; SIMULATION; ORDER; MODEL